Electrochemical Mechanism Underlying Lithium Plating in Batteries: Non-Invasive Detection and Mitigation - Sourav Das; Pranav Shrotriya (Energies)
Efficient, sustainable, safe, and portable energy storage technologies are required to reduce global dependence on fossil fuels. Lithium-ion batteries satisfy the need for reliability, high energy density, and power density in electrical transportation. Despite these advantages, lithium plating, i.e., the accumulation of metallic lithium on the graphite anode surface during rapid charging or at low temperatures, is an insidious failure mechanism that limits battery performance. Lithium plating significantly shortens the battery’s life and rapidly reduces capacity, limiting the widespread adoption of electrical vehicles. When lithium plating is extreme, it can develop lithium dendrites, which may pass through the separator and lead to an internal short circuit and the subsequent thermal runaway damage of the cell. Over the last two decades, a large number of published studies have focused on understanding the mechanisms underlying lithium plating and on approaches to mitigate its harmful effects. Nevertheless, the physics underlying lithium plating still needs to be clarified. There is a lack of real-time techniques to accurately detect and quantify lithium plating. Real-time detection is essential for alleviating lithium plating-induced failure modes. Several strategies have been explored to minimize plating and its effect on battery life and safety, such as electrolyte design, anode structure design, and hybridized charging protocol design. We summarize the current developments and the different reported hypotheses regarding plating mechanisms, the influence of environmental and electrochemical conditions on plating, recent developments in electrochemical detection methods and their potential for real-time detection, and plating mitigation techniques. The advantages and concerns associated with different electrochemical detection and mitigation techniques are also highlighted. Lastly, we discuss outstanding technical issues and possible future research directions to encourage the development of novel ideas and methods to prevent lithium plating.